The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/alz.12355
|View full text |Cite
|
Sign up to set email alerts
|

Health utility in preclinical and prodromal Alzheimer's disease for establishing the value of new disease‐modifying treatments—EQ‐5D data from the Swedish BioFINDER study

Abstract: Quality of life and health utility are important outcomes for patients with Alzheimer's disease (AD) and central for demonstrating the value of new treatments. Estimates in biomarker‐confirmed AD populations are missing, potentially delaying payer approval of treatment. We examined whether health utility, assessed with the EuroQoL‐5 3‐level version (EQ‐5D‐3L), differed between individuals with a positive or negative amyloid beta (Aβ) biomarker in patients with mild cognitive impairment (MCI) and cognitively un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A recent cross-sectional study among biomarker-confirmed AD patients in the SCD and MCI stages showed no significant difference in EQ-5D score between amyloid-positive and amyloid-negative SCD patients and a somewhat counter-intuitively higher EQ-5D score in amyloid-positive MCI patients compared to amyloid-negative MCI [ 10 ]. We confirmed these results and we also observed higher GDS in amyloid-negative MCI patients compared to amyloid-positive patients (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent cross-sectional study among biomarker-confirmed AD patients in the SCD and MCI stages showed no significant difference in EQ-5D score between amyloid-positive and amyloid-negative SCD patients and a somewhat counter-intuitively higher EQ-5D score in amyloid-positive MCI patients compared to amyloid-negative MCI [ 10 ]. We confirmed these results and we also observed higher GDS in amyloid-negative MCI patients compared to amyloid-positive patients (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study among biomarker-confirmed AD patients in the SCD and MCI stages showed no difference in the EQ-5D utilities between amyloid-positive and amyloid-negative individuals with subjective cognitive decline (SCD) and a higher EQ-5D utility in amyloid-positive mild cognitive impairment (MCI) patients compared to amyloid-negative MCI [ 10 ]. However, the cross-sectional nature of this former study does not allow insight in the trajectory of QoL over time in individuals.…”
Section: Introductionmentioning
confidence: 99%
“…13 CSF amyloid-β (Aβ) 40 and Aβ42 were analyzed by EURO-IMMUN ELISAs (EUROIMMUN AG Lübeck, Germany). Pathologic Aβ accumulation was considered as present using a previously established CSF Aβ42/40 cutoff <0.088, 20 i.e., determined by using mixture modeling statistics in the healthy controls and participants with SCD and MCI in BioFINDER. 21,22 Tau phosphorylated at Thr181 (P-tau) were analyzed with INNOTEST ELISA (Fujirebio Gent, Belgium).…”
Section: Biomarkersmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a debilitating neurodegenerative disorder and a primary cause of dementia resulting in reduced life expectancy [ 1 , 2 ], loss of function and autonomy [ 1 , 3 ], impaired quality of life (QoL) [ 4 ], care partner burden [ 5 – 7 ], and high costs to society [ 8 , 9 ]. Recent estimates suggest that 32 million people have dementia due to AD worldwide and 69 million mild cognitive impairment (MCI) due to AD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%